ANALISIS SWOT PROGRAM PEMBERDAYAAN EKONOMI UMAT PADA SENTRA BUDI DAYA JAMUR TIRAM - Kania Saraswati Harisoesyanti (Komitmen: Jurnal Ilmiah Manajemen, 2023)
The community economic empowerment program at the oyster mushroom cultivation center in Village X which is run by the UM Amil Zakat Institution (LAZ) is intended to improve the economy of the target community. In the process, an economic empowerment program requires an analysis of the organization and its environment so that future program strategies can be identified. Aims to describe and analyze the strengths, weaknesses, opportunities and threats in a community economic empowerment program, this study uses qualitative methods, with a descriptive research type. Information regarding the strengths, weaknesses, opportunities and threats of program management was taken through literature studies related to LAZ, economic empowerment, and swot analysis; the observation was carried out at the oyster mushroom cultivation center; as well as in-depth interviews involving members, administrators, center managers, LAZ UM, residents around the center and local government. The results of the study indicate that there are several strengths, including the large quantity of human resources, support from stakeholders and members. The weaknesses of this program are communication problems between the institution and the community, and the lack of a 'sense of belonging' to center members. In fact, there are various opportunities such as oyster mushroom product diversification, opportunities to establish new partners, and the creation of other activities that can be developed through oyster mushroom cultivation centers. In addition, the existence of this program is inseparable from threats from outside the center, namely the existence of a group of people who are considered to want to destroy the center's business and reduce consumers.